LO76: Emergency department procedural sedation in elderly patients. (15th May 2017) - Harris, A.; Butler, M.B.; Watson, M.
Abstract : Introduction: The use of procedural sedation and analgesia (PSA) for the performance of Emergency Department (ED) procedures has been reported to be safe and effective. However, few studies have evaluated the safety of PSA in the elderly, with conflicting results. Our primary objective was to determine if elderly patients undergoing PSA for the management of an orthopedic injury had an increased risk of adverse events (AEs) during the procedure.Methods: This retrospective review of prospectively recorded data between 2006 and 2016 included patients aged ≥16 years undergoing PSA at a single institution to facilitate treatment of a fracture or dislocation. Patients were separated into 3 age groups for analysis: young (18-40), middle-aged (41-64) and elderly (≥65). Elderly patients were divided into 3 subgroups. The primary AEs studied include hypoxia (Sp O2 <90 %) and hypotension (systolic blood pressure <100 mmHg, or >15% reduction from baseline if initial <100 mmHg). Logistic regression (LR) models tested for associations between age and outcome measurements. Effect sizes were described as odds ratios (OR) and 95% confidence intervals.Results: 4171 patients were studied, including 1125 patients ≥65 years of age. More than 90% of the time, propofol was used as a single agent sedative. Fentanyl was given as an analgesic adjunct in 88% of patients. Medication dosing declined as patients aged. In the young group, the average total propofol dose was 2.34 mg/kg compared to 1.42 mg/kg in the elderly (≥85 years subgroup: 1.07 mg/kg). Despite this, hypoxia was more likely to occur in elderly patients (2.3%) compared to younger patients (0.4%). LR models demonstrated that hypoxia was more likely to occur in: the elderly [OR 4.29 (1.58, 11.70)], patients with an ASA classification score of 3 or higher [OR 4.71 (1.89, 11.70)], and higher dosing of fentanyl in the elderly [OR 2.35 (1.21, 4.57)]. Oral or nasal airway, assisted ventilation, and suctioning were required in less than 1% of all patients. Endotracheal intubation was never required. Hypotension was more likely in elderly patients (11.6%) than younger patients (8.3%).Conclusion: When performing PSA, clinicians should be aware of the increased risk of AEs in the elderly, particularly hypoxia, and modify selection, dosing, and administration of the PSA medication(s) appropriately. Future study should examine the intermediate and long-term outcomes of elderly patients following ED PSA.